2001
DOI: 10.1034/j.1399-5618.2001.030208.x
|View full text |Cite
|
Sign up to set email alerts
|

ECT in bipolar and unipolar depression: differences in speed of response

Abstract: The BP/UP distinction had no predictive value in determining ECT outcome. In contrast, there was a large effect for BP patients to show more rapid clinical improvement and require fewer treatments than unipolar patients. The reasons for this difference are unknown, but could reflect a more rapid build up of anticonvulsant effects in BP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
1
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(111 citation statements)
references
References 32 publications
8
97
1
5
Order By: Relevance
“…As similar to this study and other studies, ECT has the highest response rate of all treatments for acute episodes of bipolar depression and major depression 15,16,17 14 ) do not differentiate bipolar from unipolar depression and the indications remain the same in both-emergency treatment needing rapid and definitive response, pregnant women with depression, high suicidal risk, patients with good response to ECT, severe psychomotor retardation, poor response of drugs in the past. Most importantly, patient and their relatives may also choose ECT as treatment for their depression.…”
Section: Resultsupporting
confidence: 75%
“…As similar to this study and other studies, ECT has the highest response rate of all treatments for acute episodes of bipolar depression and major depression 15,16,17 14 ) do not differentiate bipolar from unipolar depression and the indications remain the same in both-emergency treatment needing rapid and definitive response, pregnant women with depression, high suicidal risk, patients with good response to ECT, severe psychomotor retardation, poor response of drugs in the past. Most importantly, patient and their relatives may also choose ECT as treatment for their depression.…”
Section: Resultsupporting
confidence: 75%
“…Electroconvulsive therapy (ECT), for example, typically results in remission in 1-3 weeks (Daly et al, 2001), whereas Interpersonal Psychotherapy (IPT) (Klerman et al, 1984) or Cognitive Therapy (CBT) (Beck et al, 1979) may take 6-10 weeks. With medications, remission may begin within 4-12 weeks (or longer) after beginning treatment (O'Leary et al, 2000;Chilvers et al, 2001;Trivedi et al, 2001Trivedi et al, , 2006Quitkin et al, 2003).…”
Section: Factors Affecting Remissionmentioning
confidence: 99%
“…In the study of Sienaert et al, 5 bipolar depressed patients (n = 13) required approximately 7-8 treatments to achieve response or remission status, whereas unipolar depressed patients (n = 51) required, on average, 9-11 treatments to achieve response or remission. Likewise, in a reanalysis of data by Daly et al, 6 bipolar patients (n = 66) showed a 54.9% reduction (SD = 31.9%) in HDRS score compared with a 43.9% reduction (SD = 29.8%) among unipolar patients (n = 162) after 6 ECT treatments.…”
mentioning
confidence: 86%